2018
DOI: 10.1155/2018/9375967
|View full text |Cite
|
Sign up to set email alerts
|

Study of Clinical Characteristics and Cytokine Profiles of Asthmatic Children with Rhinovirus Infection during Acute Asthma Exacerbation at National Hospital of Pediatrics

Abstract: Background In children with asthma, the viral infection of airways is usually a main cause of acute asthma exacerbation and hospitalization. However, few studies on clinical and biomolecular characteristics of asthmatic children in this field have been done, especially in emergent countries. Objective This study described the clinical and biological characteristics of asthmatic children who had acute asthma exacerbation and rhinovirus (RV) infection. Methods Children under 15 years of age hospitalized for acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…The high number of asthma patients with a severe PAS score (44%) was associated with a high number of children diagnosed with HRV [63]. The researchers also found that the percentage of leukocytes in asthmatic children with HRV was significantly higher, compared to children without HRV (76.2% vs. 59.6%, p < 0.05) [63]. No enterovirus longitudinal studies from birth to childhood were available, assessing asthma development; however, studies have been done in children with a diagnosis of asthma [64].…”
Section: Respiratory Syncytial Virusmentioning
confidence: 98%
See 4 more Smart Citations
“…The high number of asthma patients with a severe PAS score (44%) was associated with a high number of children diagnosed with HRV [63]. The researchers also found that the percentage of leukocytes in asthmatic children with HRV was significantly higher, compared to children without HRV (76.2% vs. 59.6%, p < 0.05) [63]. No enterovirus longitudinal studies from birth to childhood were available, assessing asthma development; however, studies have been done in children with a diagnosis of asthma [64].…”
Section: Respiratory Syncytial Virusmentioning
confidence: 98%
“…Of the 115 children diagnosed with an asthma exacerbation, there were 18.2% with a mild PAS, 37.4% with a moderate PAS, and 44% with a severe PAS [63]. Nguyen-Thi-Dieu and colleagues found that 54.8% of the asthmatic children were positive for HRV [63]. The high number of asthma patients with a severe PAS score (44%) was associated with a high number of children diagnosed with HRV [63].…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
See 3 more Smart Citations